Karjalan pyhät kertomukset : tutkimus livvinkielisen alueen legendaperinteestä ja kansanuskon muutoksista - Järvinen, Irma-Riitta (Suomalaisen Kirjallisuuden Seura, 2004)
Karelian Sacred Narratives A study of Orthodox religious legends and changes in folk belief in the Livvian-speaking area of Karelia In the Livvian-speaking area of Karelia – also known as Border Karelia – an oral tradition of sacred narratives still thrived before the Second World War. In the parish of Salmi, which belonged to Finland and was situated in the border area, this tradition was much stronger than in any other parish in Ladoga Karelia. The reason behind this was that culturally Salmi was part of Olonets Karelia on the Russian side, and had been in lively contact with the region until Finland gained independence in 1917. Thus, a culturally unified area was split into two separate parts. The cross-cultural contact in the area had included visits to the monasteries of Solovki and Svir, and receiving wandering beggars and singers of religious songs (called stiihut) from the Olonets side during the Christmas and Easter periods. In addition, the ideas of the ’Old Believers’ were expressed in the numerous sacred legends and myths of origin told throughout the region. Characteristic of this region were rich and deep-rooted forms of folk piety, which included rituals to pay homage to the holy figures of Orthodox Christianity, as well as concepts and beliefs concerning the spirits’ interference in human life and their capacity to help mortals on earth. This study focuses on the sacred legends collected from Salmi in the 1930’s and 1940’s. The narrative structures of these legends are analysed according to the basic principles for structural analysis outlined by Vladimir Propp. The aim of structural analysis is firstly to present a clear description of the narrative content of this specific folklore genre, and secondly to draw some conclusions as to what kind of ideological messages this genre bears. The results of this structural analysis show that the roles of these tales in sacred legends are those of the holy figure, the opponent of the holy figure, and of the human being. The types of action are the ...